Arbacia - Gianguzza P. (Elsevier B.V., 2020)
Arbacia is unique among shallow echinoid genus, not in line with the general rule that sea urchins should be either entirely tropical or entirely temperate, with limited overlap in the subtropics. Six extant Arbacia species have been described by Mortensen. The genus Arbacia has a Neotropical origin and four different fossil species have been described from the Late Miocene. Over the past century, Arbacia has been the subject of intense investigations into the cell biology, toxicology, biochemistry, and embryology. Recently, renewed interest in this genus arose from its phylogeny, ecology, and its resilience to ocean warming and acidification. According to several studies, impacts of ocean acidification on Arbacia, growth from the juvenile to mature adult life-stage transition, seems to be mitigated by warming. Functional studies have shown that some Arbacia species play an important role in the ecology of rocky reefs. Manipulative experiments have shown a leading role of Arbacia species in maintaining the coralline barren habitat. All species of Arbacia are omnivorous, with a strong tendency to carnivory. They are able to scrape fleshy algae, sea grasses, encrusting algae, barnacle shells, and hard calcareous tubes of polychaetes from the substrata, thanks to their large Aristotle's lantern, indicative of a durophagic habit. Arbacia is a gonochoric genus with a very early maturity. Generally, Arbacia species show a reproductive cycle that is typically annual or semiannual.